2020
DOI: 10.1186/s13007-020-00694-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cytokinin sensor TCSv2 in arabidopsis and tomato

Abstract: Background Hormones are crucial to plant life and development. Being able to follow the plants hormonal response to various stimuli and throughout developmental processes is an important and increasingly widespread tool. The phytohormone cytokinin (CK) has crucial roles in the regulation of plant growth and development. Results Here we describe a version of the CK sensor Two Component signaling Sensor (TCS), referred to as TCSv2. TCSv2 has a different arrangement of binding motifs when compared to previous TC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Reducing CK in a LA deficient background shortens the morphogenetic window, partially rescuing the super compound phenotype of FIL>>miR319 ( Fig 6F ). In addition, similar to the arabidopsis TCP4, we found that LA reduced leaf sensitivity to CK, as evident from both the reduced signal of VENUS driven by the synthetic CK responsive promoter TCSv2 [ 68 ] in La-2/+ primordia ( Figs 6G–6I and S8 ), and the increase in CK-dependent anthocyanin accumulation in LA deficient plants. As expected, in WT leaf primordia, the mean TCSv2 signal decreases during development ( S8G Fig ), as the CK signal decreases, while the corrected total fluorescence increases ( S8H Fig ), because the area being measured is larger as the primordia grows.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Reducing CK in a LA deficient background shortens the morphogenetic window, partially rescuing the super compound phenotype of FIL>>miR319 ( Fig 6F ). In addition, similar to the arabidopsis TCP4, we found that LA reduced leaf sensitivity to CK, as evident from both the reduced signal of VENUS driven by the synthetic CK responsive promoter TCSv2 [ 68 ] in La-2/+ primordia ( Figs 6G–6I and S8 ), and the increase in CK-dependent anthocyanin accumulation in LA deficient plants. As expected, in WT leaf primordia, the mean TCSv2 signal decreases during development ( S8G Fig ), as the CK signal decreases, while the corrected total fluorescence increases ( S8H Fig ), because the area being measured is larger as the primordia grows.…”
Section: Resultssupporting
confidence: 73%
“…Reducing CK in a LA deficient background shortens the morphogenetic window, partially rescuing the super compound phenotype of FIL>>miR319 (Fig 6F). In addition, similar to the arabidopsis TCP4, we found that LA reduced leaf sensitivity to CK, as evident from both the reduced signal of VENUS driven by the synthetic CK responsive promoter TCSv2 [68] (E-G) Phenotypes of leaves with reduced GA response (FIL>>PROΔ17), or increased CLAU and reduced GA response (FIL>>CLAU+ PROΔ17), or reduced CK content (FIL>>CKX) treated with GA. (H-J) Effect of GA treatment on WT and clausa. All leaves depicted are fully expanded fifth leaves.…”
Section: Plos Geneticssupporting
confidence: 58%
“…In turn, ARR-5/7/15 and ARR-16, like that found in A. thaliana [83], might constrain shoot regeneration to later points (>24 hae), when CK levels rise again. The use of fluorescent sensors for auxin and CK responses, such as DR5rev::3XVENUS-N7 and TCSv2::3XVENUS [84], will allow a detailed study of the auxin and CK crosstalk during wound-induced de novo organ formation and the subsequent identification of the gene regulatory networks involved through fluorescence-activated cell sorting (FACS) coupled to single-cell RNA sequencing (scRNA-seq) [85].…”
Section: Discussionmentioning
confidence: 99%
“…A. thaliana cv. Columbia transgenic plants overexpressing pTCS::3XVENUS [ 39 ] or pARA6::ARA6-Venus [ 27 ] were germinated on 1/2 MS (Duchefa M0225) agar plates containing 50 ug/mL kanamycin, and grown upright in a growth chamber at 22 °C under short-day conditions (8 h:16 h, light:dark).…”
Section: Methodsmentioning
confidence: 99%
“…thaliana cv. Columbia transgenic plants overexpressing pTCS::3XVENUS [39] or pARA6::ARA6-Venus [27] were germinated on 1/2 MS (Duchefa M0225) agar plates…”
Section: Plant Growth Conditionsmentioning
confidence: 99%